(untitled) (Research, Society and Development, 2020)
The aim of this research is to analyze spirituality for people living with HIV / AIDS through the procedural approach of the theory of social representations. It is a qualitative, descriptive study guided by the framework of the Theory of Social Representations. 32 people who live with the Human Immunodeficiency Virus (HIV) participated through semi-structured interviews, attended at the specialized outpatient service of a state university hospital located in the city of Rio de Janeiro. The material from the corpus from the interviews, was analyzed using the IRAMUTEQ, software detailing the content related to representations, confirming the practice of spirituality as a sense of reconstruction and re-signification of life from the confrontation of living with AIDS, presenting definitions of spirituality and its relationship with the daily lives of those living with the syndrome. From the result of the study, it can be inferred that spirituality is a practice combined with health care that promotes well-being and positively influences the search for better self-care. In view of this, it is worth highlighting the importance of including spirituality in the care process, as it has a direct relationship with those who live with the syndrome and are part of their daily lives.